2017
DOI: 10.5897/err2017.3220
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the concept fraction of primary school students: The investigation in Vietnam

Abstract: In Vietnam, primary school students explicitly learn the concept of fraction in Grade 4 and 5. Because this concept is introduced to them intuitionally, it is difficult for them to understand and apply it. Base on this point, we believe that the students will commit many errors when solving exercises related to this concept. The survey of 478 students showed that some remarkable errors were made by most students; when learning fractions, students still did not understand the nature of fractions as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 2 publications
0
6
0
2
Order By: Relevance
“…However, Simon et al (2018) have indicated that promoting a deep understanding of the concept of fractions continues to be a challenge for both teachers and learners. Moreover, learners who have limited foundational knowledge concerning solving problems involving concepts of fractions have challenges with the understanding of advanced concepts within fractions (Loc, Tong & Chau 2017). Also, a deep understanding of fractions is important for the successful transition to algebra (Pearn & Stephens 2015).…”
Section: Learning Fractions In Mathematicsmentioning
confidence: 99%
“…However, Simon et al (2018) have indicated that promoting a deep understanding of the concept of fractions continues to be a challenge for both teachers and learners. Moreover, learners who have limited foundational knowledge concerning solving problems involving concepts of fractions have challenges with the understanding of advanced concepts within fractions (Loc, Tong & Chau 2017). Also, a deep understanding of fractions is important for the successful transition to algebra (Pearn & Stephens 2015).…”
Section: Learning Fractions In Mathematicsmentioning
confidence: 99%
“…The third reason is textbook reliance. Most textbooks put more emphasis on procedures and steps to solve fractions problems (Loc, Tong, & Chau, 2017). This cultivates the culture of rote memorization rather than having learners develop their own understanding of fraction concepts (Idris, 2018).…”
Section: Literature Review the Teaching Of Fractionsmentioning
confidence: 99%
“…Epistemological obstacle that appears to students in relation to fraction addition is students do not understand the concept of fractions which means they are part of the whole. Based on the results of the interview, students understand the concept of fractions is comparing the shaded parts with those that are not shaded, so that from the picture above the results of the fraction are obtained and , according to Nguyen et al (2017) that students still do not understand the nature of fractions and the equality of parts, it is because students consider the denominator and numerator in fractions as two separate integers (Şiap & Duru, 2004).…”
Section: Epistemological Obstaclementioning
confidence: 99%